Forming the structure and the properties of electric arc coatings based on high manganese steel alloyed with titanium and niobium carbides - Shihab, Shihab Thaer Abdulwahhab; Prysyazhnyuk, Pavlo; Andrusyshyn, Roman; Lutsak, Lyubomyr; Ivanov, Olexandr; Tsap, Igor (Eastern-European Journal of Enterprise Technologies, 2020)
The formation of the phase composition, structure, and properties of electric-arc coatings by electrode materials based on high-manganese austenite steel, which is strengthened by twinning steel alloyed by titanium and niobium carbides, was studied. Hardfacing alloys were applied using flux-cored arc welding (FCAW), which consisted of a shell of low-carbon steel filled with a powder mixture containing ferrosilicon manganese, graphite, rutile, fluorite, carbide of niobium or titanium. The phase composition of the coatings was calculated by the CALPHAD method using the Thermo-Calc and Dictra software to simulate equilibrium and non-equilibrium alloy cooling, respectively. The results of calculations show that the cooling conditions at hardfacing lead to the formation of the structure of metastable manganese austenite and minor (0.2 % by weight) amount of carbide of cementite type M3C. This amount of the carbide phase cannot adversely affect the ability of austenite to deformation strengthening. Crystallization of titanium and niobium carbides begins at a high temperature of 2,400 K and does not affect the phase transformations of austenite into the liquid and solid state. Thus, after cooling, the coating structure mainly consists of two phases, specifically, austenite and niobium or titanium carbide MS in an amount of 9 vol. %. According to the results from studying the microstructure using scanning electron microscopy and energy-dispersive X-ray spectroscopy of the selected area, the MС carbide phase is released as evenly distributed small particles of the shape that is close to cubic. Carbide particles are mainly located inside austenite grains. Measurement of the hardness of hardfacing coatings shows that at alloying high-manganese austenite steel with niobium and titanium carbides, the hardness significantly increases in hardfacing state from 22 to 35 HRC and after cold plastic deformation from 44 to 52 HRC. The research of wear resistance under conditions of wear by the "dry sand – rubber roller" pattern shows that TiC and NbC additives can significantly (by 1.6–1.8 times) improve wear resistance of hardfacing coatings. Due to the ability to deformation strengthening in combination with high abrasion resistance, the obtained materials for hardfacing the systems Fe–Mn–Nb–Si–C and Fe–Mn–Ti–Si–C can be recommended for application to working surfaces of digging machines